Human Split-Thickness Skin Allograft: Skin Substitute in the Treatment of Burn - M Mahdavi-Mazdeh; B Nozary Heshmati; SAH Tavakoli; M Ayaz; F Azmoudeh Ardalan; M Momeni (International Journal of Organ Transplantation Medicine, 2013)
Background: Human skin allograft has been used as wound coverage for a long time; it is one of the most successful and widely used dressings for burn wounds in the world.